L‐theanine Administration Results in Neuroprotection and Prevents Glutamate Receptor Agonist‐Mediated Injury in the Rat Model of Cerebral Ischemia‐Reperfusion. (24th October 2012) - Zukhurova, Mavdzhuda; Prosvirnina, Maria; Daineko, Anastasia; Simanenkova, Anna; Petrishchev, Nikolay; Sonin, Dmitry; Galagudza, Michael; Shamtsyan, Mark; Juneja, Lekh R.; Vlasov, Timur
Abstract : While the neuroprotective effect of green tea ( Camellia sinensis ) might be explained by the presence of amino acid L‐theanine in the tea leaves, it is not known whether postischemic administration of L‐theanine could also provide neuroprotection. In the present study, we investigated the neuroprotective effect of L‐theanine (1 and 4 mg/kg) administered at 3, 12, and 24 h after reperfusion in the rat model of stroke. We also studied the effect of L‐theanine on brain injury caused by exogenous administration of N‐methyl‐D‐aspartate and α‐amino‐3‐hydroxy‐5‐methyl‐isoxazole‐4‐propionate/kainate receptor agonists during reperfusion. Rats were subjected to 30‐min middle cerebral artery occlusion followed by 48‐h reperfusion. Neurological deficit and infarct size were determined at the end of reperfusion. At 3 and 12 h, but not at 24 h of reperfusion, L‐theanine substantially reduced the size of brain infarct. Neurological status was improved when L‐theanine was administered 3, 12, and 24 h after reperfusion. Repeated intrastriatal injections of L‐theanine at a total dose of 800 µg/kg during reperfusion prevented brain injury caused by glutamate receptor agonists. In conclusion, L‐theanine at reperfusion exerts neuroprotective effect in the in vivo rat model of stroke. Local treatment with L‐theanine at reperfusion prevents glutamate receptor agonist‐mediated brain injury. Copyright © 2012 John Wiley & Sons, Ltd.